Formation testing : pressure transient and contamination analysis - Chin, Wilson C. (Hoboken, New Jersey : Scrivener Publishing, Wiley, 2014)
"The book provides more than formulations and solutions: it offers a close look at formation tester development 'behind the scenes,' as the China National Offshore Oil Corporation opens up its research, engineering and manufacturing facilities through a collection of interesting photographs to show how formation testing tools are developed from start to finish"--
3.4 Computational notes on complex complementary error function evaluation3.5 Source model -- analytical and physical limitations; 3.6 Full three-dimensional transient Darcy flow model for horizontal wells; 3.7 Phase delay inverse method and electromagnetic analogy; 3.8 Source model applications to dual packers; 3.9 Closing remarks; 3.10 References; Part II Math Models, Results and Detailed Examples; 4. Multiphase Flow and Contamination -- Transient Immiscible and Miscible Modeling with Fluid Compressibility; 4.1 Invasion, supercharging and multiphase pumping.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Reservoir oil pressure -- Testing; Contamination (Technology); Oil well logging; SCIENCE / Energy; Contamination (Technology); Oil well logging; Reservoir oil pressure -- Testing; Electronic books